Radio and X-ray observations of supernovae in dense environments. Issue Volume 12:Issue S331(2017) (17th October 2017) - Chandra, Poonam
Abstract: Here we discuss the observational properties of supernovae exploding in extremely dense environments, namely Type IIn supernovae (SNe IIn). In SNe IIn, the surrounding environments play significant role in the supernovae energetics and evolution. Thus they are different than other classes of core collapse supernovae, whose energetics are not significantly altered by their environments. Though high density of medium is a prerequisite for radio and X-ray emission, less than 10% on SNe IIn are bright in these bands. This has important implications for their progenitor models. I will discuss the radio and X-ray observations of SNe IIn, which are crucial to unravel their complex environments. We also discuss some individual supernovae belonging to this class and discuss as to how they have refined our understanding of SNe IIn. Finally the importance of well sampled long term light curves in radio and X-ray bands cannot be stressed enough.